Design and implementation of an android mobile application prototype for the University of the Philippines College of Engineering Library - Santos, Patcheska Dewi R. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
Technology has evolved greatly in a short span of time. Gadgets and all other means that can provide easier and faster access are everywhere. People always look for new and advanced developments in terms of technological capability. As everything gets diverse, libraries will not be able to fully provide the information and access that the users need if they will not be able to keep up with the rapid pace of technological developments. Mobile phones have also found their way in libraries, providing new avenues for providing services.